THE IMPACT OF MARKETING MIX ON THE PURCHASE DECISION WHEN BORROWING CONSUMER LOANS - Handry Sudiartha Athar (Univeristas Islam Bandung, 2021)
The purpose of this study was to determine the importance of the influence of the marketing mix, consisting of products, prices, places, promotions, physical evidence, people and processes on the customer's decision to borrow consumer credit, and to find out which of the seven marketing mix variables had the most impact dominant in the customer's decision to borrow consumer credit from PT. Bank NTB Syariah. This study is a descriptive study with both a population and a sample of 50 people obtained by non-probability techniques that is, using targeted sampling. Data collection techniques used were interviews, observation and documentation. This type of research data is quantitative data and qualitative data. Data sources used are primary data and secondary data. Data analysis was performed by multiple regression analysis with the F test to test the significance of the relationship of the seven independent variables along with the dependent variable. The results showed that 1) the marketing mix of services consisting of products, prices, promotions, places, people, processes and physical evidence had a significant impact on customer loan decision making; 2) Process variables have the most dominant influence on the customer's decision to borrow consumer credit from PT. Bank NTB Syariah.